Digital LKPD with Educandy on Neighborhood Topic in Elementary School - Tazkia, A'Shoka Najma; Irdiyansyah, Iyan; Destiana, Dita (Jurnal Al Burhan, 2025)
Development of a Digital Student Worksheet (LKPD) using the Educandy application. This research aims to enhance the learning experiences of fourth-grade students. The study involved 28 participants and assessed the effectiveness of the LKPD on the topic "What was the area where I used to live?". The results indicated a high level of usability, with a score of 88% from students, signifying it as very suitable for learning processes. Additionally, teacher feedback was even more positive, achieving a score of 92%, confirming its appropriateness for educational use. The study also employed the ADDIE model (Analyze, Design, Development, Implementation, Evaluation) for development, which received validation scores of 94% from language experts, 100% from media experts, and 92% from content experts. The practicality of the LKPD was further supported by student and teacher responses, which scored 88% and 92%, respectively.